Особенности геомагнитных вариаций в северной части территории Армении - А. О. Симонян; М. В. Оганян; А. С. Хачатрян (ՀՀ ԳԱԱ հրատ.)
В работе решается проблема выделения локальных геомагнитных вариаций на фоне вариаций внешних источников и глобального характера вариаций, генерированных в жидком ядре Земли процессами, тесно связанными с генерацией и поддержкой ее магнитного поля. Выделены особенности геомагнитных вариаций, характерных для пунктов измерений в северной части территории Армении.Աշխատանքում փորձ է արված առանձնացնել տեղական երկրամագնիսական վարիացիաները արտաքին աղբյուրների և գլոբալ բնույթի Երկրի մագնիսական դաշտի վարիացիաների շարքում: Նկարագվում են ՀՀ տարածքի հյուսիսային մասում դիտարված երկրամագնիսական վարիացիաների առանձնահատկությունները:The problem of separation of local anomalies of geomagnetic variations from the variations of external origins and global feature geomagnetic variations generated in the Earth’s deep interiors due to the processes closely connected with the generation and maintenance of its magnetic field is being solved. In the process of separation of geomagnetic variations, which are specific for measurement points in the northern part of the territory of Armenia the regional scale variations of internal origins were evaluated and removed from observational data temporal series by use of high-accuracy IGRF models and the external origins regional variations were estimated and removed using the temporal series of solar and geomagnetic activity indices.
Keywords: Science; Geology; Geophysics